PENGARUH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA SEKTOR INFRASTURKTUR, UTILITAS DAN TRANSPORTASI DI INDONESIA - Regina Yosef Windu Kusuma (Business Accounting Review, 2016)
The research on the influence of Corporate Social Responsibility (CSR) to the value of the company had been done a lot previously, but the results of these studies were not consistent and specific research on the Infrastructure sector, Utilities, and Transportations had been never done yet.This study was conducted to know the affect of CSR on firm value on Infrastructure sector, Utilities, and Transportation. The CSR was proxied by using the Global Reporting Initiative (GRI) Index 3.1 and the value of the company was proxied by using Tobin's Q. There were three control variables in this study: firm size, market share and the debt to equity ratio. The sample use din this study were 43 companies with 175 observations in the infrastructure sector, Utilities, and Transportation in 2009-2013 study period.The results showed that CSR and the debt to equity ratio does not affect to the value of the company. While firm size negatively affected company value, and market share affected the company value.